The contribution of realist evaluation to critical analysis of the effectiveness of entrepreneurship education competitions. Issue 6 (December 2018) - Brentnall, Catherine; Rodríguez, Iván Diego; Culkin, Nigel
The purpose of this article is to explore the effectiveness of entrepreneurship education (EE) programmes through the lens of realist evaluation (RE). The interest of the authoring team – a practitioner–academic mix with professional experience including developing EE in primary and secondary schools – lies with EE competitions, a type of intervention recommended for and delivered to students and pupils of all ages. RE is a theory-driven philosophy, methodology and adaptable logic of enquiry with which to conceptualize and analyse such programmes. In this study, we undertake an act of 'organized scepticism', as described by evidenced-based policy academic Ray Pawson, to identify and question the declared outcomes of EE competitions in European policy over a 10-year period. However, our contribution goes beyond the application of an evaluation approach, novel to EE. We argue that, while education generally, and EE specifically, appears committed to emulating 'gold standard' scientific evaluation approaches (e.g. randomized controlled trials, systematic review and meta-analysis), the field of evidenced-based policymaking has moved on. Now, alternative methodological strategies are being embraced and RE in particular has evolved as an approach which better aligns knowledge production with the reality of complex, socially contingent programmes. By using this approach, we not only establish that education and psychology theories challenge the outcomes of EE competitions declared in policy, but also demonstrate the wider relevance of RE to the appraisal and refinement of the theorizing and practice of entrepreneurship programmes and interventions.